2019
DOI: 10.2196/13503
|View full text |Cite
|
Sign up to set email alerts
|

A Smart and Multifaceted Mobile Health System for Delivering Evidence-Based Secondary Prevention of Stroke in Rural China: Design, Development, and Feasibility Study

Abstract: Background Mobile health (mHealth) technologies hold great promise in improving the delivery of high-quality health care services. Yet, there has been little research so far applying mHealth technologies in the context of delivering stroke care in resource-limited rural regions. Objective This study aimed to introduce the design and development of an mHealth system targeting primary health care providers and to ascertain its feasibility in supporting the delivery of a S… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 31 publications
1
40
0
Order By: Relevance
“…Such a design could reduce contamination within clusters and enhance the feasibility of implementation. Over a 1-year period in preparation for the trial, we conducted extensive contextual field research on intervention design, technology development, and a 3-month pilot study in 4 villages [ 15 , 18 , 19 ]. We then conducted the main trial in 50 rural villages in rural China to evaluate the effectiveness of the intervention with embedded process evaluation and economic evaluation.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Such a design could reduce contamination within clusters and enhance the feasibility of implementation. Over a 1-year period in preparation for the trial, we conducted extensive contextual field research on intervention design, technology development, and a 3-month pilot study in 4 villages [ 15 , 18 , 19 ]. We then conducted the main trial in 50 rural villages in rural China to evaluate the effectiveness of the intervention with embedded process evaluation and economic evaluation.…”
Section: Methodsmentioning
confidence: 99%
“…The study is reported according to the CONSORT guidance for reporting cluster-randomized trial ( S1 Checklist ) [ 20 ]. The trial protocol, technological development, and statistical analysis plan were published in detail [ 15 , 18 , 19 , 21 ]. We describe a condensed version below.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Team-based care involving specialists and community health workers to empower, encourage, and facilitate care processes for patients with a prior acute CVD event has shown improvements in medication adherence and systolic blood pressure [11]. Prior studies have also demonstrated the feasibility of implementing quality improvement (QI) strategies, leading to improvements in cardiovascular risk factor control, prescription of guideline-directed medical therapy, and quality of life among patients with a prior acute coronary syndrome event or stroke and among those at high predicted cardiovascular disease risk [12][13][14].…”
Section: Introductionmentioning
confidence: 99%